Comparison Of Hospital Marketing Team Knowledge Before And After Digital Marketing Strategy Training - Latifa Noor, Hesty; Susanto, Anton; Sophia Chrisnanda, Stevina (LPPM Universitas Duta Bangsa Surakarta, 2024)
Umi Barokah Boyolali Hospital is a type D hospital in Boyolali Regency. Currently, the marketing team at Umi Barokah Boyolali Hospital is starting to pioneer the development of digital marketing efforts through various social media which is expected to increase patient visits. Problems that exist in terms of marketing include high competition between hospitals which is one of the factors that patient visits at Umi Barokah Hospital Boyolali tend to fluctuate, the marketing team's lack of knowledge regarding Digital Marketing, there are still many job desks for each member of the marketing team that are not yet ideal and the lack of supporting equipment results in less than optimal digital marketing efforts. The marketing strategy that is currently being implemented is still not optimal considering that views on various social media for hospitals are still lacking. This research carried out an intervention to measure the knowledge of the marketing team before and after carrying out training related to the Digital Marketing Hospital Transformation Strategy which combines Media Content Marketing, Collaboration Transformation, Expanding Social Media Networks, Optimizing Patient Services through digital marketing. The research was carried out in August 2024 at Umi Barokah Boyolali Hospital. The subjects in this research were the Hospital marketing team of 16 people consisting of the social media, public relations and customer relations sections of Umi Barokah Boyolali Hospital. After carrying out the pre-test and post-test, the median pre-test knowledge score was 40, while The median post-test knowledge score was 80. The results of bivariate analysis were p=0.000. There was a significant difference in participants' knowledge before and after training.